2019
DOI: 10.14309/ajg.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Pentazocine, a Kappa-Opioid Agonist, Is Better Than Diclofenac for Analgesia in Acute Pancreatitis: A Randomized Controlled Trial

Abstract: OBJECTIVES: The ideal analgesic is not known for patients with acute pancreatitis (AP). Concerns have been raised about serious adverse effects of opioid analgesics increasing the severity of AP. We hypothesized that nonsteroidal anti-inflammatory drugs might be better analgesics because of their anti-inflammatory effect. Our objective was to compare pentazocine, an opioid, and diclofenac, a nonsteroidal anti-inflammatory drug, for adequate analgesia in patients with AP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…Opioids are reported to decrease the need of supplementary analgesia ( n = 162, 3 studies) in acute pancreatitis highlighting their efficacy (Basurto Ona et al, ). In a recently published study, pentazocine was found to be more effective than diclofenac in patients of AP by providing longer pain free intervals and decreased need for rescue analgesia (Mahapatra et al, ). In our study, although tramadol decreased the need of supplementary analgesia (40% in diclofenac group vs. 25% in tramadol group), the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are reported to decrease the need of supplementary analgesia ( n = 162, 3 studies) in acute pancreatitis highlighting their efficacy (Basurto Ona et al, ). In a recently published study, pentazocine was found to be more effective than diclofenac in patients of AP by providing longer pain free intervals and decreased need for rescue analgesia (Mahapatra et al, ). In our study, although tramadol decreased the need of supplementary analgesia (40% in diclofenac group vs. 25% in tramadol group), the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A PRISMA flow diagram for study selection is shown in Figure 1. A total of 12 studies (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) were included. Study design and quality assessment are displayed in Table 2 and a detailed Jadad scoring is shown in Supplementary Table 1.…”
Section: Design and Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…A total of 800 patients with AP were screened and 699 were analysed with age ranged from 23 to 86 years old. Gender was reported in 11 studies (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Two studies (39,40) reported the weight and 3 studies (35-37) reported body mass index.…”
Section: Baseline Characteristics Of Included Patientsmentioning
confidence: 99%
See 2 more Smart Citations